Pengaruh Gaji, Kepemimpinan, dan Motivasi terhadap Kinerja Karyawan SPPBE PT Mitha Jaya Kusuma Siasem, Wanasari - Brebes - Amey, Vivian Pushein Margaretha; Afridah, Nur; Indriyani, Azizah; Riono, Slamet Bambang; Harini, Dwi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the impact of salary, leadership, and motivation on employee performance at SPPBE PT Mitha Jaya Kusuma Siasem, Wanasari, Brebes. The company, despite a stable workforce of 45 employees, has experienced challenges such as low employee retention, dissatisfaction with compensation, and inconsistent leadership effectiveness. Addressing these issues, the research aims to analyze how the three variables affect performance both individually and simultaneously. A quantitative method was employed using a survey distributed via Google Forms, with data analyzed through multiple linear regression using SPSS. Validity and reliability tests confirmed the quality of the instrument, while classical assumption tests indicated normality, no multicollinearity, and homoscedasticity. The findings reveal that salary does not significantly influence employee performance when tested independently. However, leadership and motivation show a significant and positive effect. Furthermore, when tested simultaneously, salary, leadership, and motivation together have a significant influence, accounting for 82% of the variation in performance. Among the three, motivation is identified as the most dominant factor. The study suggests that while financial compensation alone may not improve outcomes, leadership quality and intrinsic motivation play a more substantial role in boosting performance. Therefore, companies should focus on leadership development and motivation enhancement alongside fair compensation to optimize employee productivity.